The thin obstacle problem for some variable coefficient degenerate elliptic operators. (October 2022) - Banerjee, Agnid; Buseghin, Federico; Garofalo, Nicola
Abstract: In this paper, we establish the optimal interior regularity and the C 1, γ smoothness of the regular part of the free boundary in the thin obstacle problem for a class of degenerate elliptic equations with variable coefficients.